The religious kibbutz movement. The revival of the Jewish religious community. Comp. and ed. by A. Fishman. [With contribs of M. Unna, T. Admanit, S. Friedman a.o.] (Religious section of the Youth and Hechalutz Department of the Zionist Organization, 1957)
With index and map.